A Dysprosium Metallocene Single‐Molecule Magnet Functioning at the Axial Limit. Issue 38 (13th July 2017) - Guo, Fu‐Sheng; Day, Benjamin M.; Chen, Yan‐Cong; Tong, Ming‐Liang; Mansikkamäki, Akseli; Layfield, Richard A.
Abstract: Abstraction of a chloride ligand from the dysprosium metallocene [(Cp ttt )2 DyCl] (1Dy Cp ttt =1, 2, 4‐tri( tert ‐butyl)cyclopentadienide) by the triethylsilylium cation produces the first base‐free rare‐earth metallocenium cation [(Cp ttt )2 Dy] + (2Dy ) as a salt of the non‐coordinating [B(C6 F5 )4 ] − anion. Magnetic measurements reveal that [2Dy ][B(C6 F5 )4 ] is an SMM with a record anisotropy barrier up to 1277 cm −1 (1837 K) in zero field and a record magnetic blocking temperature of 60 K, including hysteresis with coercivity. The exceptional magnetic axiality of2Dy is further highlighted by computational studies, which reveal this system to be the first lanthanide SMM in which all low‐lying Kramers doublets correspond to a well‐defined MJ value, with no significant mixing even in the higher doublets. Abstract : SMMashing : A dysprosium(III) metallocenium cation is a single‐molecule magnet (SMM) with a record anisotropy barrier of 1277 cm −1 and record magnetic blocking up to 60 K, including hysteresis with coercivity.